Towards the effective legal regulation of Waqf in Nigeria: problems and prospects - Oseni, Umar Aimhanosi (Institute of Objective Studies, 2012)
The importance and need to utilize the economic benefits of waqf cannot be overemphasized in the current global economic conditions. In order to become part of the global move towards the revival of awqaf, Nigeria, a country predominantly dominated by Muslims, needs to enact laws to regulate the management of awqaf properties. This paper examines the current state of waqf in Nigeria, issues affecting the institution of waqf and the extent of its regulation with an appraisal of the existing laws. It is argued that the provision of the Constitution of Nigeria 1999 subjecting waqf to the jurisdiction of the Shari'ah Court of Appeal without any further regulation in the form of an Act does not augur well for the needs of Nigerian Muslims and the economy of the country. In fact, the so-called Muslim States in the country are still groping in the darkness of colonial laws of trusts. The paper concludes that the economic benefits of awqaf can only be harnessed when there is effective legal regulation in the country, and by that, the economic benefits of the institution will be felt by all.